2021
DOI: 10.1093/brain/awab079
|View full text |Cite
|
Sign up to set email alerts
|

Painful and non-painful diabetic neuropathy, diagnostic challenges and implications for future management

Abstract: Peripheral neuropathy is one of the most common complications of both type 1 and type 2 diabetes. Up to half of patients with diabetes develop neuropathy during the course of their disease, which is accompanied by neuropathic pain in to 30–40% of cases. Peripheral nerve injury in diabetes can manifest as progressive distal symmetric polyneuropathy, autonomic neuropathy, radiculo-plexopathies, and mononeuropathies. The most common diabetic neuropathy is distal symmetric polyneuropathy, which we will refer to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
140
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(147 citation statements)
references
References 128 publications
0
140
0
7
Order By: Relevance
“…Quantitative sensory testing is a suitable tool to non-invasively assess and monitor sensory nerve function in response to controlled stimuli (small fibre function: cold, warmth, pain; large fibre function: vibration) 3 4. Temperature detection thresholds will be determined at the thenar eminence and dorsum of the foot (TSA-II NeuroSensory Analyzer, Medoc, Ramat Yishai, Israel), while vibration perception thresholds (VPTs) will be assessed at the second metacarpal bone and medial malleolus (Vibrameter, Somedic, Stockholm, Sweden).…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative sensory testing is a suitable tool to non-invasively assess and monitor sensory nerve function in response to controlled stimuli (small fibre function: cold, warmth, pain; large fibre function: vibration) 3 4. Temperature detection thresholds will be determined at the thenar eminence and dorsum of the foot (TSA-II NeuroSensory Analyzer, Medoc, Ramat Yishai, Israel), while vibration perception thresholds (VPTs) will be assessed at the second metacarpal bone and medial malleolus (Vibrameter, Somedic, Stockholm, Sweden).…”
Section: Methods and Analysismentioning
confidence: 99%
“…DSPN is associated with considerable morbidity, increased mortality, foot ulcers and markedly impaired quality of life by causing neuropathic pain and sleep deprivation 2. Neuropathic symptoms include particularly pain, paraesthesia and numbness, while neuropathic signs comprise sensory deficits to touch, pressure, temperature and pain stimuli 2 3. However, DSPN frequently remains an underdiagnosed and undertreated condition as therapy options are limited 4…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that approximately one-third of individuals with DM are a icted with DNP over their disease course (Wang et al, 2014). Clinically, the predominant features of DNP include spontaneous pain, allodynia, and hyperalgesia (Jensen et al, 2021). More importantly, DNP has been well-regarded as a crucial risk factor that exerts an impact on the quality of life and life expectancy among DM patients (Selvarajah et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis is complex and multifactorial and includes immune-mediated, inflammatory, vascular, and metabolic pathways [2,3]. The clinical manifestations of classical diabetic symmetrical polyneuropathy (DSPN) include sensory and motor loss of the peripheral nerves to feet and hands, evident as a "stocking-and-glove" distribution mirroring a length-dependent axonopathy of the larger sensory and motor nerves in the extremities [4]. Thus, patients experience a number of paradoxical sensory deficits ranging from loss of protective sensation/numbness to debilitating neuropathic pain [5].…”
Section: Introductionmentioning
confidence: 99%